(untitled) (Dhaka University Journal of Biological Sciences, 2022)
An experiment was conducted to study the effect of textile wastewater on growth and yield components of rice (Oryza sativa L.). The treatments wereT1: Control, T2: Sole RDF (Recommended Dose of Fertilizer) + FW (Fresh Water), T3: 50% RDF + 25% TWW (Textile Waste Water), T4: 50% RDF + 50% TWW, T5: 50% RDF + 75% TWW, T6: 50% RDF + 100% TWW. The highest plant height (134.1 cm), tiller number at maturity stage (344/m2), straw yield (6.94 t/ha),grain yield (4.25 t/ha), panicle number (306/m2), panicle length (24.57cm), number of grain/ panicle (118.5), percent of filled grain/panicle (85.07%) and 1000-grain weight (13.77gm) were found inT2. And the second highest plant height (124.2 cm), tiller number at maturity stage (342/m2), grain yield (3.97 t/ha), panicle number (301/m2), panicle length (24.12cm), number of grain per panicle (117.2), percent of filled grain/panicle (84.17%) and 1000-grain weight (13.37gm) were found in T4.And T5 gave the second highest yield of straw (6.05 t/ha). Although highest values were found in T2, but statistically the achievements indicate that there was little difference between the T2 and T4 treatments. The overall findings of this study indicated that where fresh water is scarce application of 50% RDF along with 50% TWW irrigation may be a good indicator to achieve better growth and yield of rice. Dhaka Univ. J. Biol. Sci. 31(1): 147-157, 2022 (January)